Penerapan Web Interaktif Climate Kids untuk Membangun Pemahaman Konsep dan Kesadaran Lingkungan Siswa Kelas VI Pada Materi Pemanasan Global - Irma Aulia; Atep Sujana; Cucun Sunaengsih (Jurnal Penelitian Pendidikan IPA, 2024)
There is a problem faced, namely that elementary school students' understanding of science concepts is still low, which has an impact on low environmental awareness. This research aims to determine the application of the Climate Kids interactive web to build students' conceptual understanding and environmental awareness. The method used in this research is quantitative with an exploratory approach and pre-Exploratory with a one group pretest-posttest design. Participants in this research involved 25 students, 10 male students and 15 female students in class VI of one of the state elementary schools in West Bandung Regency, West Java Province. The research results show that the Climate Kids interactive web can build conceptual understanding and environmental awareness as seen from the average pretest score of 37.67 while the posttest average score is 79.87, supported by the results of the Wilcoxon test with asymp. Sig. 0.000 < 0.05, which means there is a significant difference between the pretest-posttest results and the average environmental awareness questionnaire results obtained are 92%, which shows that the level of students' environmental awareness after being given learning is in the very high category.